2016
DOI: 10.1088/2053-1591/aa50c1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of pentagonal atomic chains in BCC Fe nanowires

Abstract: For the first time, we report the formation of pentagonal atomic chains during tensile deformation of ultra thin BCC Fe nanowires. Extensive molecular dynamics simulations have been performed on <100>/{110} BCC Fe nanowires with different cross section width varying from 0.404 to 3.634 nm at temperatures ranging from 10 to 900 K. The results indicate that above certain temperature, long and stable pentagonal atomic chains form in BCC Fe nanowires with cross section width less than 2.83 nm. The temperature, abo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…With the increase of strain, some grain boundaries are fractured and recombined, and some dislocations are generated from one side of the grain boundary, grow up and penetrate the whole grain, and then annihilate on the other side of the grain boundary. Sainath et al observed a similar phenomenon in their study [30]. In this process, a large number of slip bands are generated, and the proportion of HCP lattice structure is also significantly increased.…”
Section: Effect Of Strain Rate On Properties Of Nanopolycrystalline Cu-sn Alloysupporting
confidence: 56%
“…With the increase of strain, some grain boundaries are fractured and recombined, and some dislocations are generated from one side of the grain boundary, grow up and penetrate the whole grain, and then annihilate on the other side of the grain boundary. Sainath et al observed a similar phenomenon in their study [30]. In this process, a large number of slip bands are generated, and the proportion of HCP lattice structure is also significantly increased.…”
Section: Effect Of Strain Rate On Properties Of Nanopolycrystalline Cu-sn Alloysupporting
confidence: 56%
“…The atomic chain consists of a central atom sandwiched between the two pentagonal rings, where each pentagonal ring consists of 5 atoms. Formation of pentagonal atomic chains has been reported in <100> BCC Fe and Fe-Cr nanowires at high temperatures for ultra thin cross-section width less than 2.83 nm 13,42 . The transformation of perfect BCC lattice into the pentagonal structure has been described in terms of energy minimization 42,43 .…”
Section: B Deformation and Failure Behaviormentioning
confidence: 99%
“…76 Studies are also present for 1D pentagonal materials referred to as penta-twinned nanowires; however, only elemental and non-ionic pentagonal NWs have been experimentally realized [77][78][79] or theoretically proposed. [80][81][82][83] In this article, we study the structural, electronic and topological properties of the SnTe pentagonal NWs with [110] orientation. Compared to the literature, 13 our system differs in its [110] orientation, periodicity along the z-direction and in hosting a core chain (CC) that produces peculiar properties.…”
Section: And Cubicmentioning
confidence: 99%
“…76 Studies are also present for 1D pentagonal materials referred to as penta-twinned nanowires; however, only elemental and non-ionic pentagonal NWs have been experimentally realized 77–79 or theoretically proposed. 80–83…”
Section: Introductionmentioning
confidence: 99%